Development of ultrasonic tomography for composition determination of water and oil flow - Ng, Wei Nyap (2005)
This project presents an implementation of the ultrasonic tomography to determine the composition of the water and oil flow. The transmission method of ultrasonic tomography is implemented in this project as the ultrasonic waves can propagate through both the medium of water and oil. This method is also one of the non-invasive methods that do not disturb the internal flow of the pipeline. The velocity of ultrasonic waves varies in water, oil and different composition of water and oil. The composition of water and oil can be determined from the measurement of this propagation time. Therefore, the design of the electronic circuits is to measure the propagation time of the ultrasonic waves through the medium. There are sixteen pairs of ultrasonic sensor mounted non-invasively around the periphery of an acrylic pipe. The grease is used as the coupling material to mount these ultrasonic sensors. The ultrasonic sensor used is 40 kHz of its frequency and 125o of its beam angle. The beam angle of the ultrasonic sensor is preferred to be wider to provide wider visualization area. In this project, different composition of water and oil are used and the propagation times of the ultrasonic waves through the medium are then measured. These measurements are read into the computer through the data acquisition system (DAS) card. The cross-sectional-image is reconstructed by a custom-created software using Microsoft Visual Basic 6.0. The image reconstruction algorithm that used in the software is linear back projection (LBP) algorithm. The composition of the water and oil of the flow is determined from the reconstructed image. The composition of the water and oil will be shown in numerical forms and their distribution in the flow could be seen from the image. In this thesis, the results obtained from the project are presented. The implementation method, reconstructed images and analysis of the results are also presented in this thesis. This system can be implemented and bring benefits to the oil production industries.